The nature of changes in human geography since the 1980s: variation or progress? - Christian Kesteloot; Pieter Saey (Belgeo)
This paper concerns the changes in human geographical research over the last 20 years as far as the mainstream Anglo-Saxon publications are concerned. We contend that although a lot of continuity appears through the further co-existence of the three broad approaches in geography (regional, theoretical quantitative and radical), societal and scientific changes have brought new elements into geographical practice. They can be captured with four characteristics: human geography is holographic, ethnographic, constructivist and institutionalist. The two first characteristics are metaphors of the geographical empirical stance that seeks to unveil the whole within the parts and the symbolic order behind everyday practice. The two others are more essential and point to the fact that geography now explicitly examines the socio-spatial reality as a social product shaped by and reshaping human institutions. As a result geography has made a lot of progress. It uses more relevant concepts to engage in clarifying the problems of our time, the physical environment is reintroduced in human geography as a hybrid category and the old opposition between the idiographic and nomothetic approaches is finally transcended. However, there are limits to the postmodern constructivist stance, which imply that radical geography remains a crucial component of human geography in order to explicit problems of social justice.